2019
DOI: 10.3389/fevo.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

A Floral Diet Increases the Longevity of the Coccinellid Adalia bipunctata but Does Not Allow Molting or Reproduction

Abstract: Adalia bipunctata L. (Coleoptera: Coccinellidae) is a generalist aphidophagous coccinellid and an important natural enemy in many agroecosystems including orchards. Coccinellid species have been observed to consume non-prey food like nectar and pollen, but the value of these foods for A. bipunctata is poorly known. The objective of this study was to determine the effect of different prey and non-prey diets on A. bipunctata larval development and adult longevity and fecundity. Larval development was studied on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…Similar plant species were considered that offer resources in flowers with a short corolla or provide extrafloral nectaries (Table 1). Here, pollen and nectar rewards are easily exploitable by flower visitors with short-tongued or unspecialized mouth parts such as many beneficial flies (Syrphidae, Tachinidae, and others), lacewings, parasitoid Hymenoptera and beetles [14,20,21,22,23,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar plant species were considered that offer resources in flowers with a short corolla or provide extrafloral nectaries (Table 1). Here, pollen and nectar rewards are easily exploitable by flower visitors with short-tongued or unspecialized mouth parts such as many beneficial flies (Syrphidae, Tachinidae, and others), lacewings, parasitoid Hymenoptera and beetles [14,20,21,22,23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Natural enemy groups, including those considered exclusively predatory can directly use nectar and pollen provided by flower strips [23,65]. However, in field studies it may be difficult to distinguish between the value of pollen and nectar versus the value of alternative prey and habitat to these predators.…”
Section: Resultsmentioning
confidence: 99%
“…Besides using a high‐quality prey diet, we also used a high‐quality floral diet, as buckwheat flowers have open nectaries, no documented toxic compounds, and are of high value to predators, including A. bipunctata (Sigsgaard et al, 2013; Bruinsma et al, 2014; Russell, 2015; van Rijn & Wäckers, 2016; He & Sigsgaard, 2019; He et al, 2021). Non‐prey foods can provide supplementary nutrients that sustain coccinellids until they locate prey (Lundgren, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Hemptinne & Desprets (1986) and De Clercq et al (2005) reported that A. bipunctata larvae were able to develop into adults on a pure pollen diet, but with a low survival rate. However, He & Sigsgaard (2019) found that whereas non‐prey diets could prolong survival time for A. bipunctata larvae, larvae did not develop beyond the first instar.…”
Section: Introductionmentioning
confidence: 99%
“…The fitness-related measurements used as reference for diet quality (development time, weight, etc.) are often complemented by biochemical analyses of the body of the predator and/or the prey [1][2][3][4][5][6][7][8][9]. The information on basic components (nitrogen, lipids and carbohydrates) of a given diet can indicate how nutritionally balanced the diet is [10].…”
Section: Introductionmentioning
confidence: 99%